FILOSOFI HUKUM KHILAFAH (Tinjauan Ontologis, Epistemologis dan Aksiologis) - A, Asmawi (Ahkam: Jurnal Hukum Islam, 2018)
The most discussed form of Islamic state system is khilafah. Therefore, this current study discusses the philosophy of khilafah from the perspectives of ontology, epistemology, and axiology. From the perspective of its ontology, it turns out that khilafah is a dynamic terminology in the history of Islamic politic. It can be traced from the history that the Islamic political system changes according to the social condition and the ruling regime. It may be called khilafah, imamah or mulk (kingdom). In other meanings, it can refer to religious theocracy, monarchy-oligarchy, or democracy in the form of nation state. Whatever the name of the Islamic state system is used, all Islamic state must be directed to achieve the maslahah. According to the scholars of the maqashid al-syariah, the maslahah is measured using the five universal standards of principles (kuliyat al-khams). They are ensuring the freedom of religion (hifdz al-din), ensuring the life (hifdz al-nafs), ensuring the creativity and freedom of thinking and speak (hifdz al-‘aql), securing the property (hifdz al-mal), and ensuring the sustainability of offspring and human dignity (hifdz al-nasl wa al-‘irdl).                Keywords: Islamic law Khilafah, Politic, Maslahah